Sosialisasi Literasi Keuangan Syariah Sebagai Upaya Peningkatan Pemahaman Ekonomi Masyarakat Desa Tamiang - Amru Hasibuan; Akhir Saleh Pulungan; Ismail Nasution; Kali Junjung Hasibuan; Gelar Praminan Pasaribu; Laila Suriati Harahap; Nur Kasima Pasaribu; Riswan Santoso (Yayasan Perguruan Kampus, 2025)
The community's low level of understanding of financial literacy, particularly Islamic finance, is one of the factors inhibiting economic growth at the rural level. This situation also occurs in Tamiang Village, Batang Lubu Sutam District, Padang Lawas Regency, where the majority of residents still manage their finances traditionally without considering Islamic principles or appropriate management strategies. This problem impacts the community's limitations in developing businesses, managing income, and accessing Islamic financial services. To address this issue, a Community Service Program in the form of